Strategies for Accelerating Sustainable Drinking Water Pipeline Utilization - Eddy Rachmad; Ahyahudin Sodri; Yuki MA. Wardhana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Uncontrolled and excessive use of groundwater leads to economic, social, and environmental impacts. This study investigated factors influencing the low willingness to utilize piped water. The research was conducted in Duren Sawit Village, East Jakarta. The study focused on the sources of household clean water and the factors affecting the low utilization of piped water. A qualitative research approach was employed through in-depth interviews with key informants selected using purposive sampling, and the problem was analyzed using a fishbone diagram. The study found 81% of households use groundwater, only 9% use piped water, and 10% use both sources. The findings reveal that 25% of the households using piped water still rely entirely on groundwater. The low utilization of piped water was influenced by several factors, including socio-economic conditions, environmental behavior, groundwater quality, performance of PAM Jaya, and groundwater regulations for household usage. Based on the analysis, strategies for accelerating piped water utilization were proposed, including socialization and education on groundwater conservation, quality of groundwater, improvement of PAM Jaya performance, and changes in regulations regarding groundwater use for household. Environmental behavior is identified as the primary factor influencing the high use of groundwater. Several strategies involving stakeholders are necessary to promote the use of piped water among households. Keywords: Environmental behaviour, Ground water, Ground water regulation, Piped water, Socio economic.